2019
DOI: 10.1523/jneurosci.0213-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Lambda Mediates Acid-Sensing Ion Channel 1a-Dependent Cortical Synaptic Plasticity and Pain Hypersensitivity

Abstract: Chronic pain is a serious debilitating disease for which effective treatment is still lacking. Acid-sensing ion channel 1a (ASIC1a) has been implicated in nociceptive processing at both peripheral and spinal neurons. However, whether ASIC1a also contributes to pain perception at the supraspinal level remains elusive. Here, we report that ASIC1a in ACC is required for thermal and mechanical hypersensitivity associated with chronic pain. ACC-specific genetic deletion or pharmacological blockade of ASIC1a reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 76 publications
1
35
0
Order By: Relevance
“…ASIC1a is a critical member of the ASICs family and mainly expressed in the brain [ 11 , 16 ]. During the physiological process, ASIC1a is involved in synaptic transmission [ 1 , 33 ], learning and memory [ 11 , 34 ], fear conditioning [ 35 ], and pain modulation [ 36 , 37 ]. For example, ASIC1a channels contribute to both long-term potentiation (LTP) and long-term depression [ 11 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASIC1a is a critical member of the ASICs family and mainly expressed in the brain [ 11 , 16 ]. During the physiological process, ASIC1a is involved in synaptic transmission [ 1 , 33 ], learning and memory [ 11 , 34 ], fear conditioning [ 35 ], and pain modulation [ 36 , 37 ]. For example, ASIC1a channels contribute to both long-term potentiation (LTP) and long-term depression [ 11 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown that changes in expression and functions of key ion channels and receptors in extrinsic sensory neurons play an important role in the abnormal pain of gastrointestinal diseases 14‐16 . Acid‐sensing ion channels (ASICs) are a class of cation channels that are directly activated by extracellular acids and belong to the degenerate protein, epithelial Na + ion channel superfamily (DEG/ENaC), which are widely distributed in central and peripheral nervous systems 17 . ASICs are divided into at least six isoforms: ASIC1a, ASIC1b, ASIC2a, ASIC2b, ASIC3, and ASIC4.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Acid-sensing ion channels (ASICs) are a class of cation channels that are directly activated by extracellular acids and belong to the degenerate protein, epithelial Na + ion channel superfamily (DEG/ENaC), which are widely distributed in central and peripheral nervous systems. 17 ASICs are divided into at least six isoforms: ASIC1a, ASIC1b, ASIC2a, ASIC2b, ASIC3, and ASIC4.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we used a central pain-sensitization model to show that BDNF upregulates the surface expression of ASIC1a in spinal dorsal horn neurons [ 57 ]. Since ASIC1a function has been implicated in synaptic plasticity [ 21 , 25 , 27 , 78 ], we asked whether membrane trafficking of ASIC1a in the dendritic and synaptic surface of cortical neurons responds to strengthening of neuronal or synaptic activity by BDNF. Here, we first showed that BDNF treatment increased the surface expression of endogenous ASIC1a in cultured rat cortical neurons, as revealed by surface biotinylation (Fig.…”
Section: Resultsmentioning
confidence: 99%